Solving this equation by substitution, It my work correct?  TOPIC_SOLVED

Simplificatation, evaluation, linear equations, linear graphs, linear inequalities, basic word problems, etc.

Solving this equation by substitution, It my work correct?

Postby illuminati58 on Tue Jul 14, 2009 4:27 pm

Can someone please tell if i am doing this right! Please!
x + Y = 6
2x + y =8

2x + y = 8
x + y = 6
x = -y + 6

2 (-y + 6) + y = 8
2y + 12 + y = 8
3y + 12 = 8
3y = - 4
y = -4/3

X = -y + 6
X = -(-4/3) + 6
x = 4/3 + 6
x = 4/3 + 6

{( 12, 4/3 +6 )}
Last edited by illuminati58 on Tue Jul 14, 2009 5:27 pm, edited 1 time in total.
illuminati58
 
Posts: 9
Joined: Sun Jul 12, 2009 11:23 pm

Sponsor

Sponsor
 

Postby stapel_eliz on Tue Jul 14, 2009 4:40 pm

illuminati58 wrote:2 (-y + 6) + 4 = 8

Where did the "4" come from?
User avatar
stapel_eliz
 
Posts: 1705
Joined: Mon Dec 08, 2008 4:22 pm

Re: Solving this equation by substitution, It my work correct?

Postby illuminati58 on Tue Jul 14, 2009 5:29 pm

Sorry it was a typo :) but my answer doesnt seem correct
x + Y = 6
2x + y =8

2x + y = 8
x + y = 6
x = -y + 6

2 (-y + 6) + y = 8
2y + 12 + y = 8
3y + 12 = 8
3y = - 4
y = -4/3

X = -y + 6
X = -(-4/3) + 6
x = 4/3 + 6
x = 4/3 + 6

{( 12, 4/3 +6 )}
illuminati58
 
Posts: 9
Joined: Sun Jul 12, 2009 11:23 pm

Re: Solving this equation by substitution, It my work correct?

Postby illuminati58 on Tue Jul 14, 2009 5:58 pm

What about this solution for the same problem?

x + y = 6
2x + y = 8

x= -y + 6
2(-y+6) + y = 8
- 2y -12 + y = 8
y - 12 = 8
y = 16

x = -y + 6
x = (-16) + 6
x = 16 + 6
x = 22

{(22, 16)}
illuminati58
 
Posts: 9
Joined: Sun Jul 12, 2009 11:23 pm

  TOPIC_SOLVED

Postby stapel_eliz on Tue Jul 14, 2009 10:42 pm

illuminati58 wrote:2 (-y + 6) + y = 8
2y + 12 + y = 8

How did (2)(-y) become 2y? :wink:
User avatar
stapel_eliz
 
Posts: 1705
Joined: Mon Dec 08, 2008 4:22 pm


Return to Beginning Algebra